INCREASING ENERGY EFFICIENCY AND RELIABILITY BY OPERATION OF ELECTRIC DRIVES THROUGH FREQUENCY CONVERTERS - Norboev, Anvar (Innovatsion texnologiyalar, 2024)
This article analyzes experimental studies and their results on increasing the energy efficiency and reliability of electric vehicles. Experimental studies of direct start-up of the electric drive and start-up through a frequency converter, the obtained results have been comparatively analyzed. The research was carried out on a 22 kW electric motor. The obtained results are presented based on a graph. The analysis of the results was researched because of the graphoanalytical method. The impact of the electric drives on the energy efficiency and reliability of the frequency converter was evaluated based on the results of the experiment. According to the results of an experiment on starting an electric drive using a frequency converter, an increase in energy efficiency by 23% and its reliability by 26% was scientifically substantiated.